Association between obesity and anxiety among an adolescent population of Rajkot district, Gujarat, India: a cross sectional and descriptive study - Patel, Dipal (International Journal of Contemporary Pediatrics, 2020)
Background: Proper good nutrition are essential for mental development, physical growth, health and wellbeing and survival of adolescents. School based data of India shows a prevalence of obesity is 5.6% to 24.0% among children and adolescents. Psychosocial complications associated with obesity include poor self-image, depression, and difficulties in both social environment and home. This study was carried out with an objective to find out prevalence of malnutrition and associated factors. Methods: A cross sectional study conducted among 1026 school going adolescents from 4 schools of Rajkot, Gujarat, India. Depression and anxiety were measured using Beck Depression Inventory and Beck Anxiety Inventory. Chi-square test was applied as test of significance. Results: Majority of the students (58.1%) were belonged to early adolescent age group. About 67.1% were males. About 16.6% were underweight and 1.2% were obese. Overweight was more prevalent in girls (5.6%) as compared to boys (1.2%). Prevalence of anxiety and depression was 9.9% and 18.5% respectively. Anxiety was frequently found in overweight and obese adolescents (82.0%) as compared to only underweight and normal adolescents (7.1%, p<0.0001). Conclusions: The prevalence rate of overweight and obesity were 9.7% and 4.3%. Girls are more affected with overweight. Significant number of adolescents was suffering from anxiety (9.9%) and depression (18.5%). Anxiety was frequently found in overweight and obese adolescents. There is need of immediate action to prevent adolescent obesity. Assessment of anxiety and depression among students with proper counselling should be carried out at least once a year.